2022
DOI: 10.31004/obsesi.v6i6.3111
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kompetensi Digital Guru PAUD dalam Mengelola Pembelajaran Daring Anak Usia Dini

Abstract: Guru PAUD di era digitalisasi ini dituntut untuk memiliki kompetensi yang memadai, baik dari segi wawasan maupun penggunaan teknologi digitalnya. Penelitian ini bertujuan untuk melihat tingkat kompetensi digital guru PAUD. Pendekatan dan metode dalam penelitian ini adalah deskriptif kualitatif. Pengumpulan data dilakukan melalui observasi dan wawancara pada 10 orang guru PAUD di Kecamatan Babakan Ciparay, Kota Bandung. Dari hasil penelitian ditemukan bahwa tingkat kompetensi digital guru PAUD pada area pembuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
1
16
0
2
Order By: Relevance
“…The activities above are beneficial and have a significant impact on the leadership development of students. Even though the activity is conducted online or virtually, where online learning is defined as knowledge gained in a direct and indirect context through the use of a device other than an internet connection, it can still result in beneficial and significant learning outcomes (Lismayanti et al, 2021;Nurhayati, 2021;Nurhayati & Musa, 2020;Winarti et al, 2022).…”
Section: Figure 1 Observation Results Diagrammentioning
confidence: 99%
“…The activities above are beneficial and have a significant impact on the leadership development of students. Even though the activity is conducted online or virtually, where online learning is defined as knowledge gained in a direct and indirect context through the use of a device other than an internet connection, it can still result in beneficial and significant learning outcomes (Lismayanti et al, 2021;Nurhayati, 2021;Nurhayati & Musa, 2020;Winarti et al, 2022).…”
Section: Figure 1 Observation Results Diagrammentioning
confidence: 99%
“…In relation to the practicum-based learning, many other studies have also revealed that practicum is proven to improve a SPS. A study has been conducted by Winarti and Nurhayati (2014) concerning project-oriented practicum learning to improve SPS and understanding the concepts. The research showed the practicum activities support students in mastering SPS.…”
Section: Discussionmentioning
confidence: 99%
“…Didalam proses ini pendampingan menjadi hal penting yang harus dilakukan baik oleh orang tua maupun guru (Winarti et al, 2022). Maka kecenderungan anak-anak untuk menyukai sejumlah aplikasi dalam smartphone seharunya mendapatkan pengawalan orang dewasa terutama oleh orang tua sehingga anak dapat memilih jenis aplikasi yang edukatif sehingga dan dapat membantu perkembangan psikomotoriknya, ini menunjukkan bahwa mengizinkan anak-anak kecil untuk terlibat dengan teknologi digital selama beberapa waktu dapat bermanfaat, asalkan anak-anak menggunakan waktu tersebut dengan baik untuk memperoleh keterampilan digital (Hurwitz & Schmitt, 2020).…”
Section: Pendahuluanunclassified